Carboplatin Hypersensitivity Reactions in Pediatric Low Grade Glioma Are Protocol Specific and Desensitization Shows Poor Efficacy. Issue 1 (24th July 2015) - Dodgshun, Andrew J.; Hansford, Jordan R.; Cole, Theresa; Choo, Sharon; Sullivan, Michael J.
Abstract : Background: The use of carboplatin for the treatment of pediatric low grade gliomas (PLGG) is often limited by the development of carboplatin hypersensitivity. Reported rates of carboplatin hypersensitivity reactions vary between 6% and 32% in these patients. Here we report the frequency of carboplatin hypersensitivity reactions depending on the treatment regimen used, and outcomes of carboplatin desensitization. Methods: The records of all patients in a single institution who were treated with carboplatin for PLGG were accessed and all patients receiving more than one dose of carboplatin are reported. Results: Thirty four patients with PLGG were treated with carboplatin according to one of the two different regimens. Carboplatin hypersensitivity was documented in 47% of patients, but the frequency differed by treatment protocol. Those patients treated with 4‐weekly single agent carboplatin had carboplatin allergy in 8% of cases whereas 68% of those treated with combined carboplatin and vincristine (every three weeks, according to the SIOP 2004 low grade glioma protocol) had carboplatin reactions (OR 23.6, P < 0.01). Desensitization was only successful in two out of 10 patients in whom it was attempted. Conclusions: Hypersensitivity reactions to carboplatin are more common in this cohort than previously reported and rates are protocol‐dependent. Desensitization showed limited effectiveness in this cohort. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.